الاندماج المصرفي و ضروراته في العالم العربي - قنوع, نزار; شريقي, طرفة; إسماعيل, رولا غازي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد القطاع المصرفي من أكثر الأنشطة تأثراً بمظاهر العولمة المالية, والتي تتمثل أهم ملامحها في التطورات والتحولات المتلاحقة التي شهدتها الساحة المالية والمصرفية الدولية, وفي مقدمتها التحرر المالي, التحول نحو البنوك الشاملة, خصخصة البنوك, إعادة هيكلة الخدمات المصرفية, التوسع في عملية الاندماج المصرفي. وانطلاقاً من أهمية هذه العناصر في زيادة القدرة التنافسية للجهاز المصرفي, كان تطرقنا لموضوع الاندماج المصرفي, محاولين التعرف على ما يتضمنه هذا التعبير الاقتصادي من معنى. The Banking sector is one of the most affected activities of financial globalization, whose features can be seen in the dramatic developments and changes in international financial and monetary system, the most important of which are financial liberation, the change towards the global banks, banks' privatization, reconstructing the banking services, and expansion in banking mergers. By considering the importance of these elements in increasing the competitive power of the banking system, we studied the banking merger, trying to find out all the implications of this economic expression.